(untitled) (Brazilian Journal of Radiation Sciences, 2021)
New laboratories for brachytherapy sources production are being implemented in our facility at IPEN, in São Paulo. A great challenge implementing a production laboratory is to comply with the Good Manufacturing Practices (GMPs), which involves process validation and all supporting activities such as cleaning and sanitization. Much more than compliance with regulatory guidelines, required for certification and inspections, a validation builds large process knowledge, provides possibilities for optimization and improvement, increasing the degree of maturity of all people involved and the quality system. The process validation results in a document that certifies that any procedure, process, equipment, material, operation or system leads to the expected results. This work focused on the new laboratory, been assembled to produce small iodine-125 seeds. The process validation was performed three times for evaluation. The parameters evaluated in this study were: the source welding efficiency and the leakage tests results (immersion test). The welding efficiency doesn’t have an established parameter, since is visually evaluated by the operator, and the leakage detection must be under 5 nCi / 185 Bq, accordingly with the ISO 9978. We observed values were average 79-87% production efficiency and leakage tests were under 5 nCi/seed. Although established values for the global efficiency aren’t available in the literature, the results showed high consistency and acceptable percentages, especially when other similar manufacturing processes are used in comparison (average 85-70% found in the literature for other similar metallic structures). Those values will be important data when drafting the validation document and to follow the Good Manufacturing Practices (GMPs).process